2010
DOI: 10.1007/s10336-010-0584-y
|View full text |Cite
|
Sign up to set email alerts
|

Winter space use and social behaviors of Chinese Grouse (Bonasa sewerzowi) at Lianhuashan mountains, Gansu, China

Abstract: Winter movement and social behavior of Chinese Grouse (Bonasa sewerzowi) were studied at Lianhuashan Natural Reserve, northwest China from 1995 to 2009. According to radio-tracking data from 25 male Chinese Grouse, their home ranges in winter ranged from 6.0 ± 1.6 ha (n = 9) to 16.0 ± 2.6 ha (n = 10). Most females and all the yearlings moved from breeding areas and formed mixed-sex flocks. However, males adopted one of three social behaviors and movement patterns, including: staying in the territory, moving to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Previous studies have found that willows are important in determining the habitat selection of Chinese Grouse during spring (Ji et al 2005), brood rearing (Zhao et al 2015), and winter seasons (Yang et al 2011). We found that willows were important in determining males' core territories during paring and egg-laying periods in this study.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have found that willows are important in determining the habitat selection of Chinese Grouse during spring (Ji et al 2005), brood rearing (Zhao et al 2015), and winter seasons (Yang et al 2011). We found that willows were important in determining males' core territories during paring and egg-laying periods in this study.…”
Section: Discussionsupporting
confidence: 68%
“…We found that willows were important in determining males' core territories during paring and egg-laying periods in this study. A much higher number of small willow trees (2328/ ha) was found in core breeding territory than winter habitat (570-1820/ha) (Yang et al 2011). Males were more sedentary after occupying territories in spring; however, many males moved around in winter when most food resources in their territories were covered by deep snow.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, territories of Spruce Grouse Falcipennis canadensis differ in spring and in winter (Allan 1985). Winter is a challenging period for individuals, due to high predation risk, shortage of food, and extreme environmental conditions Yang et al 2011). Winter habitats of Hazel Grouse were not studied in the Western Carpathians.…”
Section: Introductionmentioning
confidence: 99%